2022
DOI: 10.3389/fimmu.2022.971045
|View full text |Cite
|
Sign up to set email alerts
|

Neglected, yet significant role of FOXP1 in T-cell quiescence, differentiation and exhaustion

Abstract: FOXP1 is ubiquitously expressed in the human body and is implicated in both physiological and pathological processes including cancer. However, despite its importance the role of FOXP1 in T-cells has not been extensively studied. Although relatively few phenotypic and mechanistic details are available, FOXP1 role in T-cell quiescence and differentiation of CD4+ subsets has recently been established. FOXP1 prevents spontaneous T-cell activation, preserves memory potential, and regulates the development of folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…10c). While the role of SOX4 in CD8+T cell development is unclear, FOXP1 has been shown to maintain a quiescent profile in naive CD8+T cells 88,89 , and our results are in keeping with a more activated profile in type 1 innate T cells. ARID5B has been reported to regulate metabolic programming and promote IFNγ production in NK cells 90 .…”
Section: Supplementary Notesupporting
confidence: 85%
“…10c). While the role of SOX4 in CD8+T cell development is unclear, FOXP1 has been shown to maintain a quiescent profile in naive CD8+T cells 88,89 , and our results are in keeping with a more activated profile in type 1 innate T cells. ARID5B has been reported to regulate metabolic programming and promote IFNγ production in NK cells 90 .…”
Section: Supplementary Notesupporting
confidence: 85%
“…Loss of ACTRT1 function was reported to lead to aberrant activation of Hedgehog signalling in basal cell carcinoma 26 . Another example is Forkhead box protein 1 (FOXP1) on chromosome 3p13, which plays a role in T‐cell quiescence and differentiation 27 . Its deficiency has been reported to be correlated positively with tumour proliferation in prostate cancer or tumour origin in non‐small cell lung cancer 28 29 .…”
Section: Resultsmentioning
confidence: 99%
“…26 Another example is Forkhead box protein 1 (FOXP1) on chromosome 3p13, which plays a role in T-cell quiescence and differentiation. 27 Its deficiency has been reported to be correlated positively with tumour proliferation in prostate cancer or tumour origin in non-small cell lung cancer. 2829 These results suggest that HPV integration in the host genome may lead to the loss of function of genes that serve as tumour suppressors, thus accelerating tumourigenesis.…”
Section: Identification Of Integration Sites Co-occurred With Cnvsmentioning
confidence: 99%
“…Furthermore, increasing evidence suggests that Treg cell infiltration in the TME is closely associated with poor prognosis and that the depletion of Treg cells may activate and enhance antitumor immune responses ( 42 ). Studies have revealed that Tregs play important roles in the microenvironment, prognosis, and chemotherapy response of various tumors ( 43 ). Shang et al.…”
Section: Discussionmentioning
confidence: 99%